Design Interactive Multimedia Book Sanggar Doka Tawa Tana Using The Design Sprint Method - Harviansyah, Yushivan Rendi; Ashar, Muhammad; Akbar, Muhammad Iqbal (Journal of Disruptive Learning Innovation (JODLI), 2022)
Tourism is a journey from one place to another carried out by a group of people or individual for a certain period of time with the aim of traveling that requires planning previously. This is supported by current technological advances, one of which is multimedia technology including information technology. This multimedia technology has made a significant contribution to the tourism sector by generating the ability to promote and develop tourist objects in any location with greater ease, less cost, and more flexibility. One of the attractions that is developing at the time of current technological advances, namely the Sanggar Doka Tawa Tana. This studio is one of the leading tourist attractions in the province of NTT that can attract tourists to visit. However Due to the Covid-19 outbreak, the number of tourists visiting has decreased drastically. But in 2021 the number of tourists visiting began to increase. So in this research development of EPUB-based interactive multimedia books to promote and provide the latest information for potential tourists related to the Sanggar Doka Tawa Tana. On book design interactive multimedia of Sanggar Doka Tawa Tana, the method used is the design sprint method where In the method there are 5 frameworks, namely understand, diverge, decide, prototype and validate.